Performance Analysis of Ieee 802.15.7-Based Visible Light Communication Systems in Underground Mine Environments - Seguel-Gonzalez, F (Springer, 2022)
Underground mining (UM) is an industry worldwide known for its hostile work environment; therefore, a proper communication system is essential to preserve the miners’ safety. However, the irregular features of UM tunnels as well as their environment prone to electromagnetic interference make it difficult to implement traditional wireless communication systems. Therefore, a viable solution is to complement the systems with a communication infrastructure based on visible light communication (VLC). Nevertheless, VLC systems for underground mines have not been widely developed, although there is extensive literature on VLC applications in indoor non-hostile environments. This article develops a study and characterization of the physical factors and external phenomena of the UM tunnels, as well as the orientation of optical components that affect the performance of VLC systems. In order to evaluate and verify the behavior of the UM-VLC channel, the channel impulse response (CIR) and the received optical power distribution in the UM scenario are presented. Furthermore, to analyze the performance of the UM-VLC system, the bit error rate (BER) curves are obtained based on the IEEE 802.15.7 standard considering perfect and imperfect channel state information (CSI), and by using the least square (LS), minimum mean square error (MMSE), and spectral temporal averaging (STA) channel estimation techniques. The metrics analyzed show and validate the adverse effects of the UM environment on the VLC system and its channel, which gives a solid baseline to find proper solutions and mitigate those effects. © 2022, The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature.
Keywords: Channel modeling; scattering; shadowing; underground mining; visible light communication (VLC)